Sustainable development as open system of activity - Najder-Stefaniak, Krystyna (Studia Ecologiae et Bioethicae, 2019)
The author of the paper treats the notion of sustainable development as a project of understanding the reality and storage of knowledge that has been filling with content since the moment it was introduced into the discourse of science. She shows that the ecosystem metaphor helps to propose the main theses of the speech: (1) sustainable development is a system of activity that enriches the social and natural environment of people; (2) to understand its specifics supports the metaphor of life; (3) sustainable development must be an open, relatively isolated system. The notions of life, sustainable development, creative persistence and transgression are the keys to the presented considerations.